ANTIOXIDANT AND ANTI CLASTOGENIC POTENTIAL OF PIPER LONGUM L. - D., Archana; M., Dixitha; S., Santhy K. (International Journal of Applied Pharmaceutics, 2015)
Objective: Present study was aimed to evaluate the antioxidant and anti clastogenic potential of methanol extract of Piper longum L (MEPL). Methods: Chromatographic analysis was carried out using thermo GC-Trace Ultra Ver: 5.0 GC-MS. Antioxidant activities were assessed by DPPH free radical scavenging assay and reducing power assay. Based on the antioxidant activity, micronuclei formation in peripheral blood lymphocytes was analyzed. The protection afforded by Piper longum L. against the cytotoxicity of peripheral blood lymphocytes were confirmed by the micronucleus (MN) assay. Results: The GC-MS analysis provides different peaks determining the presence of eighteen phytochemical compounds with different therapeutic activities. The methanol extract at a concentration of 40 Î¼g/ml showed the highest antioxidant activity by DPPH assay (68.42%) comparable to standard, ascorbic acid (73.68%). The reducing power observed was in the order of 40 Î¼g/ml>20 Î¼g/ml>10 Î¼g/ml. MEPL treatment decreased the frequency of MN in a concentration dependent manner. Conclusion: A substantial amount of bioactive components are present in Piper longum L. A good correlation of the antioxidant capacity of the plant was established by different assay methodologies. MN test confirmed the anti clastogenic potential in peripheral blood lymphocytes. Keywords: Piper longum L., MEPL, GC-MS, DPPH, reducing power, Micronuclei.